STRAETGI DAKWAH KIAI ABDUL GHOFUR DALAM MAQOLAH AGOMO IKU NOTO APIKE KOYO OPO SEJE DESO SEJE CORO DI DESA SENDANGAGUNG KECAMATAN PACIRAN KABUPATEN LAMONGAN - Miftachul Ulum; Lathifatun Nisa’ (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
In an effort to support the success of da'wah, a da'i is required to have wise strategies and have methods as a process in social institutions and awareness of the people. Strategy is a necessity to achieve a desired goal. In essence, strategy is a series of plans to achieve the desired goal. If it is related to the da'wah process, strategy has a very important role in the movement of da'wah activities, so that a da'i is required to have a strategy and method of building people's awareness. This research uses qualitative research with a type of approach through Ferdinan De Searsure's semiotic analysis. The flow of this research follows the concept of a da'wah approach, namely using a sociological da'wah approach and an anthropological da'wah approach.The results of this research indicate that the da'wah strategy in maqolah KH. Abdul Ghofur